Incorporating batik fabric in pendant design inspired by Malay Pendant (Dokoh) / Fatin Nurulhuda Rosley - Rosley, Fatin Nurulhuda (2016)
This research is about the styling of Batik in the design of jewellery accessory with pendant concept. This research also focuses on styling of modern pendant. This is because, pendant has been forgotten by today’s generation especially teenagers. So that, styling of pendant must be expanded widely in today’s generation’s daily attire to uphold the Malay traditional style. In making sure that it is becoming a style in the society, a few methods have been taken to ensure that the styling of Batik in the design of jewellery accessory with pendant concept always become a trend. There are three research objectives which are: i) to identify the types of pendant from the past until today, ii) to identify the changes on pendant design from the past and pendants that are available in today’s market. Iii) Suggestion to produce three designs of accessory product of pendant chosen by users in styling of Batik